Analisis Model Biaya-Manfaat Dengan Kegunaan Pada Berbagai Fase Siklus Hidup Produk - Dedi Karmana; Mira Ismirani Fudsyi; Sakti Muda Nasution; Zen Munawar; Herru Soerjono (LPPM POLITEKNIK LP3I BANDUNG, 2024)
Cost/benefit analysis is a risk assessment technique that helps users choose or decide which treatment options need to be taken for a risk. This research aims to conduct a usability analysis from a cost benefit model, because not all organizations carry out development that fully integrates usability activities as an integral part of the product development project. In the process, the cost/benefit analysis will consider the level of cost efficiency and the level of benefits that can be obtained from each available treatment. The more efficient the costs incurred and the higher the benefits obtained from a risk treatment, the greater the tendency for that treatment to be chosen. The reason for conducting the analysis is that there are usability benefits that are better invisible to management. In this study, the characteristics of the utility cost utility model are explained. The cost-benefit model has a different approach in identifying, approaching, and categorizing costs, benefits and uses. The model described will provide useful general guidelines for reflecting the costs and benefits of usability. The results of this research recommend that the type of development business organization and product type be developed as variables that can be taken into account when analyzing benefits so as to obtain better usability.